2005
DOI: 10.1002/pssb.200540110
|View full text |Cite
|
Sign up to set email alerts
|

First‐principles study of the pressure‐induced αω transition in titanium

Abstract: The pressure-induced transition from the α to the ω-phase of Ti is studied with first-principles totalenergy calculations by a procedure that finds the equilibrium structures of each phase directly as a function of pressure from minima of the Gibbs free energy. Good to excellent agreement with experiment is found for the lattice parameters of the two phases both at zero pressure and as functions of pressure up to 900 kbar. The Gibbs free energies of the two phases at zero temperature and without zero-point ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
9
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 23 publications
7
9
0
Order By: Relevance
“…Therefore, c/a also somehow shows a slight increase in terms of temperature from 1.585 at ambient temperature to 1.590 at 923 K (650°C) (Figure 3(b)). This finding is actually in good agreement with both the theoretical [25] and the experimental reports. [3][4][5]15] IV.…”
Section: Resultssupporting
confidence: 93%
“…Therefore, c/a also somehow shows a slight increase in terms of temperature from 1.585 at ambient temperature to 1.590 at 923 K (650°C) (Figure 3(b)). This finding is actually in good agreement with both the theoretical [25] and the experimental reports. [3][4][5]15] IV.…”
Section: Resultssupporting
confidence: 93%
“…The extrapolation of experimental data [30] predicted that a martensitic α → ω transition occurs near −1 GPa at 0 K. Our results are within the hysteresis interval (−5 to +8 GPa) and remain in excellent agreement with the other experimental and theoretical works [9,18,31]. Theoretical investigations [9] were carried out using first-principles total-energy calculations and the EBP for finding the equilibrium structures directly as a function of the pressure from the minima of the particular Gibbs free energies.…”
Section: -4supporting
confidence: 90%
“…These results are summarized in table 2. Theoretical work Pressure [9] 50 GPa [18] 6 GPa [31] −3 GPa This work 0 GPa Based on the comparison between this paper's calculated pressure-induced transition and the extrapolated data from experiments, it can be suggested that this method can also be used for explaining the structural sequence in Ti under pressure for other phases.…”
Section: -4mentioning
confidence: 97%
See 2 more Smart Citations